2021
DOI: 10.1016/j.xpro.2021.100780
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for efficient CRISPR-Cas9-mediated knock-in in colorectal cancer patient-derived organoids

Abstract: Summary Patient-derived organoids (PDOs) recapitulate the cellular heterogeneity of the original colorectal tumor tissue. Here, we describe a protocol to generate genetically modified PDOs to investigate cancer stem cells. This protocol uses the CRISPR-Cas9 system to knock-in the IRES-EGFP-P2A-iCaspase9 cassette into the 3′ UTR of the potential cancer stem cell marker gene, which allows us to investigate their potential for self-replication and pluripotency. We describe the procedure for generating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Despite this revolutionary success, there remains an urgent need for increased simplicity and efficiency of genome editing in research organisms. Protocols for efficient knock-in in cultured organoids [ 179 ] and Japanese rice fish [ 180 ] have succeeded, yet nothing has been reported in mammals to this point. Moreover, previous studies were undertaken that demonstrated a synergistic interaction between the transcription factors NFAT and MEF-2 in regulating MB gene expression patterns in the muscle [ 181 ].…”
Section: Potential Therapeutic Implications Of Mb In Bat-mediated Ene...mentioning
confidence: 99%
“…Despite this revolutionary success, there remains an urgent need for increased simplicity and efficiency of genome editing in research organisms. Protocols for efficient knock-in in cultured organoids [ 179 ] and Japanese rice fish [ 180 ] have succeeded, yet nothing has been reported in mammals to this point. Moreover, previous studies were undertaken that demonstrated a synergistic interaction between the transcription factors NFAT and MEF-2 in regulating MB gene expression patterns in the muscle [ 181 ].…”
Section: Potential Therapeutic Implications Of Mb In Bat-mediated Ene...mentioning
confidence: 99%
“…Here, we have shown an effective delivery methodology for the CRISPR-Cas9 system called “nanoblades,” which permitted to obtain high levels of gene editing (20%–80%) in human and mouse organoids without the requirement for enrichment via drug selection or fluorescent reporter isolation. 33 These are levels of gene editing that are otherwise exclusively achieved in iPSC-derived organoids. 34 Brain organoids, for example, are solely derived from iPSCs and since gene editing is performed at the level of the iPSCs, which is highly efficient, deleting genes or introducing genes (e.g., oncogenes) can be performed with ease.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have shown a novel delivery methodology for the CRISPR/Cas9 system called 'nanoblades', which permitted to obtain high levels of gene editing (20%-80%) in human and mouse organoids without the requirement for enrichment via drug selection or fluorescent reporter isolation (Okamoto et al, 2021). These are levels of gene editing that are otherwise exclusively achieved in induced pluripotent stem cells (IPSC ) derived organoids (Son et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The method uses a donor template coding for an expression cassette driving a fluorescent protein such as GFP flanked by homologous genome sequences (homology arms). Through recombination at the DSB induced by Cas9, this template permitted easy identification of KO/knock-in organoids through GFP expression (Okamoto et al, 2021). Alternatively, a NHEJ strategy relying on the piggybac-transposase system to integrate hygromycin/GFP was used to screen for fluorescence or drug resistance (Artegiani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%